Real-time Patient Experience Surveys Lead to Better Scores - Keith Willner (Western Journal of Emergency Medicine)
Introduction: The patient satisfaction survey is a controversial fixture of modern emergency care. Patients who are satisfied are more likely to adhere to the treatment plan and less likely to pursue legal action. However, the current surveys are susceptible to recall bias. This study uses an analysis of data collected in a separate study to assess how patients rated their physicians’ care when asked key questions in person by a trained volunteer versus in the Doctors section of the Press Ganey (PG) survey. Methods: This was an analysis of prospectively collected data obtained in a separate study evaluating how patients experience their emergency care when learners are present. Trained medical student volunteers administered the survey to a convenience sample of patients slated for discharge at a single, community, tertiary-care hospital emergency department (ED) for a total of 12 weeks between June–October 2022. We compared this with the hospital’s PG data for the questions on which the survey was based. Results: A total of 625 patients were approached over the study period with 313 agreeing to participate (response rate 50.1%). There were 8,460 patients discharged from the ED during those times (overall rate 3.70%). During the contemporaneous PG study quarter, the ED received 266 responses during the shifts for which the study enrolled patients, of a total 8,460 discharged from the ED during those times (response rate 3.14%). All key questions favored the in-person survey vs mailed PG survey: “I felt informed” score 79.2 (262) vs 75.6 (265), P = .02; “I felt like my [doctor] took time to listen” 85.0 (261) vs 79.6 (266), P = .05; and “satisfaction with care team” 83.0 (263) vs 74.7 (265), P = .0013. Conclusion: This study shows higher satisfaction scores with an in-person survey. There was also a dramatically improved response rate compared with mail in PG forms, suggesting less recall bias. An absolute 5-point difference in PG score could lead to a relative 30-point change in percentile rank. This was a limited, single-site study whose results are hypothesis-generating but suggest a new pursuit for administrations seeking to improve their scores and possibly better understand patients’ experience of their care.